2011
DOI: 10.1007/s11431-010-4257-0
|View full text |Cite
|
Sign up to set email alerts
|

Progress and recent trend in MILD combustion

Abstract: Moderate or intense low oxygen dilution (MILD) combustion plays a significant role in the mitigation of combustion-generated pollutants and greenhouse gases whilst meeting thermal efficiency needs. However, due to the lack of the fundamental knowledge on this combustion, there is a misconception that MILD combustion should be established by high preheating of the air, which has limited its application. Our research and development on this combustion has been performed for several years. We have found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(84 citation statements)
references
References 67 publications
1
82
0
1
Order By: Relevance
“…In spite of a number of activities for industrial furnaces, the application of flameless combustion in the gas-turbine combustion system is in the preliminary phase [44]. The results from techno-economic analysis of Wang et al showed that the COSTAIR and FLOX cases had technical and economic advantages over SCR [45].…”
Section: • Low Acoustic Oscillation Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of a number of activities for industrial furnaces, the application of flameless combustion in the gas-turbine combustion system is in the preliminary phase [44]. The results from techno-economic analysis of Wang et al showed that the COSTAIR and FLOX cases had technical and economic advantages over SCR [45].…”
Section: • Low Acoustic Oscillation Andmentioning
confidence: 99%
“…The results from techno-economic analysis of Wang et al showed that the COSTAIR and FLOX cases had technical and economic advantages over SCR [45]. Luckerath, R., et al, investigated flameless combustion in forward flow configuration in elevated pressure up to 20atm for application to gas turbine combustors [44,46]. In a novel design of Levy et al that named FLOXCOM, flameless concept has been proposed for gas turbines by establishing large recirculation zone in the combustion chamber [47,48].…”
Section: • Low Acoustic Oscillation Andmentioning
confidence: 99%
“…An important influence factor for this behaviour is the exhaust gas recirculation rate which is enhanced by higher jet velocities and higher air numbers [11], respectively. Increasing recirculation serves to enhance the dilution of the fresh gas jets by hot flue gases [23] reducing the chemical reaction rates [24]. Simultaneously, rising jet velocity decreases the fluid dynamic time scale.…”
Section: Flame Shape and Locationmentioning
confidence: 99%
“…In the field of biomass [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64], Luo et al [50] estimated the annual generation of crop residues, animal manure and organic faction of MSW in Hebei Province, China from 2002 to 2007. Qiao et al [51] investigated the biogas recovery from microwave heated sludge by anaerobic digestion.…”
Section: Biomass Energymentioning
confidence: 99%
“…Qiao et al [51] investigated the biogas recovery from microwave heated sludge by anaerobic digestion. Li et al [52] reviewed the progress and recent trend in MILD combustion. Other relative fundamental researches such as combustion can be found in [53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Biomass Energymentioning
confidence: 99%